2022
DOI: 10.3390/app12115343
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Failure Mechanisms of HDPE Welded Geocell Junctions under Different Clamping Distances

Abstract: Geocells are three-dimensional honeycomb-reinforced geotechnical materials composed of strips and junctions. Its junctions can support and transmit forces in several directions. The performance of geocells has a considerable impact on engineering applications. However, the testing program of geocell junctions still lacks standardization, and limited research has been undertaken regarding the failure mechanisms of junctions when subjected to various stress types. In this paper, four test procedures for HDPE wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Rezekne, Latvia Proceedings of the 14 th International Scientific and Practical Conference. Volume 3,[214][215][216][217][218] The results, compared with other authors [20] - [22], are reliable and no deviations were observed in the regression analyses. They may be used and applied in engineering practice.…”
Section: • Hardnessmentioning
confidence: 52%
“…Rezekne, Latvia Proceedings of the 14 th International Scientific and Practical Conference. Volume 3,[214][215][216][217][218] The results, compared with other authors [20] - [22], are reliable and no deviations were observed in the regression analyses. They may be used and applied in engineering practice.…”
Section: • Hardnessmentioning
confidence: 52%
“…The results revealed that the tensile performance of the PET geocell strip is superior to that of the PP and HDPE geocell strips. Yang [32] conducted a series of laboratory tests on HDPE geocell strips with welding junctions, studied the effect of clamping distance on the strength of geocell strips and junctions, and presented a laying method of geocells on slopes based on the findings. The aforementioned literature studied the influence of strain rate, specimen shape and size, temperature, and clamping distance on the tensile mechanical properties of geocell strips and junctions.…”
Section: Geocell Heightmentioning
confidence: 99%
“…The test results of the strip with and without a junction also lacked comparison. Yang [24] studied the failure mechanisms of junctions under different clamping distances but did not consider the influence of the junction on the geocell strip.…”
Section: Introductionmentioning
confidence: 99%